Enhancement of Functional Ability in Supraspinatus Tendinitis Using Ultrasound and Isotonic Exercise: Case Study - Tu Lidya Ike Putri; Aurelia, Christabelle (UI Scholars Hub, 2024)
Supraspinatus tendinitis is an inflammation of the supraspinatus tendon caused by the supraspinatus muscle tendon overlapping with the caput longus bicep tendon so that friction and repetitive pressure occur over a long period of time and result in damage to the supraspinatus muscle tendon and supraspinatus tendinitis occurs. Characterized by complaints of pain around the shoulder followed by limitation of motion in the shoulder joint. The clinical question arises